Bouncing and 3D printable hybrids with self-healing properties - Tallia,F; Russo,L; Li,S; Orrin,A; Shi,X; Chen,S; Steele,J; Meille,S; Chevalier,J; Lee,P; Stevens,M; Cipolla,L; et al. (Materials Horizons, 2018)
Conventional composites often do not represent true synergy of their constituent materials. This is particularly evident in biomaterial applications where devices must interact with cells, resist cyclic loads and biodegrade safely. Here we propose a new hybrid system, with co-networks of organic and inorganic components, resulting in unprecedented mechanical properties, including “bouncy” elasticity and intrinsic ability to self-heal autonomously. They are also developed as new ‘inks’ that can be directly 3D printed. A hybrid is different from a nanocomposite because the components are indistinguishable from each other at the nanoscale and above. The properties are generated by a novel methodology that combines in situ cationic ring-opening polymerisation with sol–gel, creating silica/poly(tetrahydrofuran)/poly(ε-caprolactone) hybrids with molecular scale interactions and covalent links. Cartilage is notoriously difficult to repair and synthetic biomaterials have yet to mimic it closely. We show that 3D printed hybrid scaffolds with pore channels of ∼200 μm mimic the compressive behaviour of cartilage and provoke chondrocytes to produce markers integral to articular cartilage-like matrix. The synthesis method can be applied to different organic sources, leading to a new class of hybrid materials.